ANALISIS DISIPLIN KERJA PENDIDIK DAN TENAGA KEPENDIDIKAN DITINJAU DARI PERAN KEPALA SEKOLAH - Siti Nuril Ngin; Alifia Khoirunnisa; Anik Rodziah; Anna Sholikhah (Academica: Journal of Multidisciplinary Studies, 2021)
This study aims to describe the work discipline of teachers and employees on the awareness of implementing time discipline, regulatory discipline, and responsibility discipline. The indicators of the work discipline of teachers and employees are related to the principal's role as a leader and motivator. The leader will be an example and role model for his members in applying work discipline. Likewise, the principal of SD Ta'mirul Islam has a role as a leader and motivator in guiding teachers and employees to apply work discipline. This research is a descriptive research with case study method. The subjects of this study were principals, teachers, and librarians at SD Ta'mirul Islam Surakarta. Data collection techniques using observation, interviews, and documentation. The data analysis technique in this study used four stages, namely data collection, data reduction, data presentation, and drawing conclusions. The data validity technique of this research uses triangulation of sources by checking the truth of information from informants and analyzing. The results of the study indicate that there is a role for the principal as a leader and motivator in monitoring teacher work discipline, so that indicators of work discipline from time to time, regulations, and responsibilities can be implemented properly and orderly.Keywords: Work Discipline; Educator; Education Personnel; Principal's Role